Challenges facing an outsourcing dialysis program amid the COVID-19 pandemic: Diaverum AB experience - Alharbi, Ali; Mousa, Dujanah; Samson, Jennifer; Ahmad, Moustafa; Gomez, Lidia Romero; Alkhulayfi, Meshal; Suleiman, Eyad; Alghamdi, Saeed; Alhejaili, Fayez; Alhweish, Abdullah; Maddh, Naglaa; Bediwi, Waleed; et al. (International Journal of Infection Control, 2021)
Coronavirus disease 2019 (COVID-19), a disease caused by a novel coronavirus, is a major global human threat that has turned into a pandemic. Elderly patients and patients with comorbid conditions have a higher risk of complications and morbidity. Patients suffering from kidney disease on hemodialysis have an intrinsic fragility combined with a frequent burden of comorbidities in hemodialysis centers, a setting in which many patients are repeatedly treated in the same area. Moreover, if infected, the intensity of dialysis requiring specialized resources and staff is further complicated by requirements for isolation, control and prevention, putting healthcare systems under additional and exceptional strain. Therefore, all measures to slow if not eradicate the pandemic and to control unmanageably high incidence rates must be taken very seriously. Diaverum is a renal health services company playing a major role in providing end-stage kidney disease (ESKD) patients with optimum dialysis services. The aim of the present review is to shed light on the challenges and steps taken by an outsourcing dialysis program to provide recommendations for the prevention, mitigation, and containment of the emerging COVID-19 pandemic in hemodialysis centers.